2017
DOI: 10.15406/ijbsbe.2017.03.00052
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Contacts Testing using a Micro-Force Sensor Compatible with Biological Systems

Abstract: This paper presents the performance and reliability testing of microelectromechanical systems (MEMS) switches by using a micro-force sensor which was originally designed/used to conduct mechanical testing of biological cells. MEMS switches are key components for radio frequency (RF) applications due to their extremely low power consumption and small geometries over conventional technologies. However, unstable electrical contact resistance severely degrades the performance and reliability of such micro-switches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The problem is well understood by the MEMS community. The operation of microscopic contacts is thoroughly investigated using indenters [29][30][31], scanning probe microscopes [32,33], and homemade facilities [34][35][36][37][38]. It is demonstrated that the contact resistance rapidly decreases with increasing the force and then reaches saturation.…”
Section: Introductionmentioning
confidence: 99%
“…The problem is well understood by the MEMS community. The operation of microscopic contacts is thoroughly investigated using indenters [29][30][31], scanning probe microscopes [32,33], and homemade facilities [34][35][36][37][38]. It is demonstrated that the contact resistance rapidly decreases with increasing the force and then reaches saturation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this test setup is capable of measuring micromachined membrane force versus deflection behavior, as well as sensing micro force exerted by biological cell movements. A force sensor integrated with a piezoelectric actuator can be used to apply known, calibrated forces in μN ranges onto the membrane for verifying its spring behavior [14,15].…”
Section: Introductionmentioning
confidence: 99%